2022
DOI: 10.1002/eqe.3782
|View full text |Cite
|
Sign up to set email alerts
|

A new Distinct Element meso‐model for simulating the rocking‐dominated seismic response of RC columns

Abstract: The rocking-dominated seismic response of reinforced concrete (RC) columns is a complex mechanism that entails P-Δ effects, concrete crushing and spalling, rupture and dislocation of steel bars and stirrups, as well as combined localized failures causing splitting and shear-flexure cracking. In this paper, we present a new meso-scale numerical modeling strategy for the detailed simulation of the rocking response of slender RC columns under seismic actions. This work advances the current state-of-the-art by exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…When the inspectors work, they must take a special detection vehicle to reach the vicinity of the defect, but there are still some defect locations that cannot be reached. At this time, some researchers have used numerical simulation techniques to assess the residual capacity of the concrete elements in question [4], such as the innovative discrete element method [5,6] and the traditional finite element method [7]. However, only the overall bearing capacity of the structure can be assessed and subtle concrete defects cannot be detected.…”
Section: Introductionmentioning
confidence: 99%
“…When the inspectors work, they must take a special detection vehicle to reach the vicinity of the defect, but there are still some defect locations that cannot be reached. At this time, some researchers have used numerical simulation techniques to assess the residual capacity of the concrete elements in question [4], such as the innovative discrete element method [5,6] and the traditional finite element method [7]. However, only the overall bearing capacity of the structure can be assessed and subtle concrete defects cannot be detected.…”
Section: Introductionmentioning
confidence: 99%
“…As a very early study in this area, Housner [12] proposed a seminal framework to evaluate the seismic response of a solitary rigid block placed on a rigid base. Following this pioneering work, investigators over the world have endeavored to evaluate the rocking response of freestanding blocks, including experimental [13][14][15][16][17][18][19][20][21][22][23][24] and numerical approaches [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Early researchers have observed that a rocking motion has extremely complex dynamic characteristics and is barely "nonrepeatable" [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneering work, the seminal framework proposed by Housner [11] for the seismic response evaluation of freestanding rigid blocks has been followed by many in-vestigators, including experimental [12][13][14][15][16][17][18][19][20] and numerical efforts [21][22][23][24][25][26][27][28][29][30][31][32][33]. To predict the occurrence of overturning, Ishiyama [34] proposed overturning criteria involving the overturning acceleration and velocity, which are the minimum peak acceleration and velocity of the input excitation needed to overturn a rigid block, respectively.…”
Section: Introductionmentioning
confidence: 99%